GREEN IT AND SUSTAINABILITY - Souza, Alan Patrick Silverio; Ribeiro, Douglas Francisco (Revista Interface Tecnológica, 2023)
Technological advances bring with it numerous benefits for our lives, however if on the one hand it comes with improvements in our health (directly impacting on quality of life), social development and communication, on the other hand, it is notorious the negative aspects that accompany it, being thus easily noticed in overconsumption (which is increasingly driven by the capitalist business model),  the use of non-renewable raw material, and the increase in the emission of polluting gases such as CO2.  In this context, IT can be considered, as one of the major responsible for the worsening of this situation, since it is increasingly present in several areas of our daily life. This article aims to present the concepts of Sustainability and Green IT, evidencing that they see as an efficient response to the reduction or even resolution of the problems generated by this advance, since they have recommendations and practices aimed at this purpose. The methodology used as a basis is bibliographic research in articles, books and websites.
Keywords: Technological Progress; Sustainability; Sustainable Development; Green Information Technology